PENGARUH METODE APLIKASI VAKSINASI ANTRAKS TERHADAP SUHU TUBUH, FREKUENSI DENYUT JANTUNG DAN RESPIRASI DOMBA LOKAL - Yohanes Naileta Koli; Maxs U. E. Sanam; Yohanes T. R. M. R Simarmata (Jurnal Veteriner Nusantara, 2020)
The anthrax disease is caused by Bacillus anthracis which is Gram- positive and rod-shaped. The disease attacks the herbivores and can also be transmitted in humans. Vaccination is one way that is used for the prevention of anthrax disease. The anthrax vaccinations still use live anthrax vaccine, containing Bacillus anthracis sprouts 34F2, toxigenic and not encapsulated and contain 10 million spores / ml in50% glycerine-NaCl physiologic solution and 0.5% saponin. The success of the anthrax vaccination program is strongly influenced bythe physiological status of the animal, the vaccine used and the givenmethod of administration and dosage. The World HealthOrganization recommends that the application of anthrax vaccine be done in two inoculation schedules of the first application of ¼ doses and then followed by full dose a month later. The side effects of vaccination reactions that lead to anaphylactic shock can be monitored and prevented by first measuring the physiological status of livestock in the form of temperature, pulsus and respiration in a certain period of time. The purpose of this study to determine whether there are differences in physiological parameters such as body temperature, heart frequency and respiration of sheep who received different doses of vaccination. 12 lambs were divided: first group of control, second group of full dose (0.5 cc) and third group of preinoculation dose (0.125 cc). Parameters measured in the morning and afternoon. Data analysis using variance Analysis. The results showed that there was no significant difference in physiological parameters of body temperature, heart frequency and local sheep respiration given different methods of vaccination..